Between Peace and Conflict in the East and the West Studies on Transformation and Development in the OSCE Region - Mihr, Anja (Springer Nature, 2021)
This open access book features various studies on democratization, transformation, socio-economic development, and security issues in the Organization for Security and Cooperation in Europe (OSCE) geographical region and beyond. Written by experts and scholars working in the field of human dimension, security, transformation and development in Europe and Asia, particularly in post-soviet and communist countries, it examines the connectivity that the OSCE provides between the East and the West. The 2021 edition of this Compilation Series of the OSCE Academy presents studies on peace and conflict as well as political regime development in various member states of the OSCE as well as their economic, security and human rights performance and the challenges countries and society face currently. The OSCE is working in promoting Human Rights and Democratization under the notion of Human Dimension of ODIHR and is enhancing securitization and development policies in Eurasia, Europe, Central Asia and North America since 1991. 2021 marks the 30th anniversary on the tremendous efforts in promoting democracy, security and development. This compilation reviews some of these efforts in light of this anniversary, the achievements and shortcomings.